Fish-Tail Structured Fractal Monopole Printed Antenna with Dual Broadband Characteristics for Sub–6GHz 5G and X–Band Radar Applications - Guntamukkala Yaminisasi; Pokkunuri Pardhasaradhi; Nagandla Prasad; Boddapati Taraka Phani Madhav; Abeer D. Algarni; Sudipta Das; Mohammed El Ghzaoui (Fractal and Fractional)
This article presents a printed antenna, designed with a fractal-shaped patch with fish-tail structured outer edges, a tapered feedline, and a rectangular notch-based defected partial ground structure (DPGS). The presented design has been printed on a FR-4 substrate, which has a dielectric constant of 4.4 and a loss tangent of 0.035. The overall dimension of the proposed antenna is 24 × 40 × 1.6 mm3. The proposed fractal antenna achieved dual broad-band functionality by maintaining the compact size of the radiator. The designed fractal radiator can operate at three distinct resonant frequencies (3.22, 7.64, and 9.41 GHz), covering two distinct frequency bands, extending from 2.5 to 4.2 GHz and 7 to 9.8 GHz. A thorough parametric analysis has been carried out using CST Studio suite 2019 licensed version to achieve better performance in terms of S11 (dB), radiation efficiency, and gain over the operating frequency range. The operating bands fall within the S, C, and X bands to support sub-6GHz 5G and Radar applications at the microwave frequency range.